2011
DOI: 10.4172/2157-7439.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Some Metallic Nanoparticles by, and their Impact on Pulmonary Macrophages in Vivo as Viewed by Optical, Atomic Force, and Transmission Electron Microscopy

Abstract: Optical microscopy (OM), semi-contact atomic force microscopy (sc-AFM), and transmission electron microscopy (TEM) were applied to examine cells in the broncho-alveolar lavage fluid (BALF) obtained from rats 24 hours after instillation of different metallic particles suspended in deionised water or of water without any particles. In a comparative experiment with iron oxide Fe 3 O 4 (magnetite) particles having a mean diameter of 10 nm, 50 nm or 1 μm, it was demonstrated that, given equal mass doses, nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Table 1 presents the results of a comparative estimation of shifts in the BALF cell population in response to intratracheal instillation of gold NPs and silver nano- or microparticles carried out within the framework of the present study, in comparison with the earlier published results of a similar experiment with finer NPs of the same metals [5]. Rather than in parallel, these two experiments were carried out in different periods (2011 and 2012) and—what is especially important—with different background BALF cell counts (as can be seen from Table 1, all indices for control rats were higher in the second experiment as compared with the first one).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the results of a comparative estimation of shifts in the BALF cell population in response to intratracheal instillation of gold NPs and silver nano- or microparticles carried out within the framework of the present study, in comparison with the earlier published results of a similar experiment with finer NPs of the same metals [5]. Rather than in parallel, these two experiments were carried out in different periods (2011 and 2012) and—what is especially important—with different background BALF cell counts (as can be seen from Table 1, all indices for control rats were higher in the second experiment as compared with the first one).…”
Section: Resultsmentioning
confidence: 99%
“…Our own pilot experiments involving intratracheal instillations of NG and NS suspensions have shown that NS provokes a substantially greater increase in the cell count of the bronchoalveolar lavage fluid (BALF), and, judging from the ratio of neutrophil leukocytes to alveolar macrophages in BALF, NS is more cytotoxic for alveolar macrophages than NG [5]. These newly obtained data, however, need to be reproduced, preferably in experiments with the same NG and NS samples that would be used for comparative assessment of systemic toxicity and genotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] We experimented with NPs of iron oxide Fe 3 O 4 (magnetite) having mean diameters 10 nm, 50 nm or 1 mcm, gold (4 nm or 50 nm), silver (4 nm, 49 nm or 1.1 mcm), copper oxide (20 nm or 340 nm), nickel oxide NiO (30 nm), and manganese oxide Mn 3 O 4 (32 nm). Keeping in mind the above mentioned theoretical premises of our research, we used purposefully prepared and accurately characterized NPs of pure metals or their oxides suspended in deionized water rather than commercial nanomaterials.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, although the mean diameter The TEM images ( Figure 8) also testify to the physiological endocytosis of NPs as opposed to their direct penetration through cell membrane by diffusion, which, above any doubts, is also possible. [4][5][6] When NPs are of given dimensions, the pulmonary phagocytosis response strongly depends on their chemical nature. For instance, as can be seen from Table 2, the total cell, NL and AM counts, and the macrophage count of the BALF increased under the impact of silver NPs more than it did under the impact of virtually equidimensional gold NPs.…”
Section: Some Inferences From In Vivo Experiments With Metallic Nanopmentioning
confidence: 99%
See 1 more Smart Citation